Financial self-efficacy sebagai prediktor financial management behavior pada pengemudi ojek online (GRAB) di Kota Malang - Dwi Wahyu Utama; Tutut Chusniyah; Gamma Rahmita Ureka Hakim (Flourishing Journal, 2021)
Abstract: Financial self-efficacy is closely related with financial management behavior. When the individual's level of confidence is high, then the individual will be motivated to do everything in order to achieve his goal. Similarly, it is associated with individual behavior in managing their finances. The higher the level of efficacy or the level of individual confidence, the better or responsible for managing finances. The high level of confidence is due to individuals being able to think long in terms of financial management. The purpose of this study was to determine the effect of Financial Self-Efficacy on Financial Management Behavior in Ojek Online drivers (GRAB) in Malang. This research uses descriptive correlation method. The population of this research is Ojek Online drivers (GRAB) in Malang with 100 people who have characteristics (a) actively registered as Ojek Online drivers (GRAB) in Malang, (b) male and female sexes, (c) located at 20-35 years old. The research sample was 100 people using probability sampling techniques. In the validity and reliability test the results obtained are: (a) the scale of financial self-efficacy with 6 valid items having 0.677; (b) the scale of financial management behavior with 38 valid items with reliability of 0.950. The results of the study (1) the financial self-efficacy of Ojek Online drivers (GRAB) in Malang are in the low category; (2) financial management behavior of Ojek Online drivers (GRAB) in Malang are in a category that tends to be low. Hypothesis test results using simple linear regression obtained R value of 0.402 and R square value of 0.162, which indicates that there is an influence of financial self-efficacy on the financial management behavior of 16.2%. Conclusions obtained: (1) Ojek Online drivers (GRAB) in Malang have low financial self-efficacy. (2) Ojek Online drivers (GRAB) in Malang have a low financial management behavior. (3) Financial self-efficacy is a predictor of financial management behavior of Ojek Online drivers (GRAB) in Malang. Financial self-efficacy is low will also have a low financial management behavior. Suggestions that can be given are (1) for Ojek Online drivers (GRAB) in Malang, can improve financial self-efficacy and financial management behavior that is owned. (2) Further researchers are expected to pay more attention to the theory and measuring instruments used in the study, and to increase the number of research respondents. Keywords: financial self-efficacy; financial management behavior Abstrak: Financial self-efficacy memiliki hubungan dengan financial management behavior, yakni ketika keyakinan individu tinggi, maka individu akan semakin baik dan bertanggung jawab terhadap pengelolaan keuangan. Tingginya tingkat keyakinan dikarenakan individu mampu berpikir terkait pengelolaan keuangannya. Tujuan penelitian ini adalah untuk mengetahui pengaruh Financial Self-Efficacy terhadap Financial Management Behavior pada pengemudi ojek online (GRAB) di kota Malang. Penelitian ini menggunakan metode korelasi deskriptif. Populasi penelitian ini adalah pengemudi ojek online (GRAB) di kota Malang berjumlah 100 orang yang memiliki karakteristik (a) terdaftar aktif sebagai pengemudi ojek online (GRAB) di kota Malang, (b) jenis kelamin laki-laki dan perempuan, (c) berada pada rentan usia 20-35 tahun. Sampel penelitian berjumlah 100 orang merupakan sampel populasi. Pengambilan data menggunakan skala financial self-efficacy berjumlah 6 aitem dengan validitas 0,375-0,749 dan reliabilitas 0,677. Skala financial management behavior berjumlah 32 aitem valid dengan validitas 0,362-0,757 dan reliabilitas 0,950. Uji hipotesis menggunakan regresi linier sederhana. Hasil penelitian (1) financial self-efficacy berada dalam kategori rendah; (2) financial management behavior berada dalam kategori cenderung rendah. Hasil uji hipotesis diperoleh nilai R 0,402 dan nilai R square sebesar 0,162, berarti ada pengaruh financial self-efficacy terhadap financial management behavior dengan determinasi varian financial self-efficacy terhadap financial management behavior sebesar 16,2% dan 83,8% disebabkan oleh variabel lain. Saran yang dapat diberikan adalah (1) bagi pengemudi ojek online (GRAB) di kota Malang, dapat meningkatkan financial self-efficacy dan financial management behavior yang dimiliki. (2) Bagi peneliti selanjutnya diharapkan untuk memperluas variabel penelitian yang lainnya, seperti kontrol diri, kepercayaan terhadap uang, kepuasan terhadap keuangan, pengetahuan keuangan, sikap keuangan, tingkat pendapatan, dan demografi. Kata kunci: financial self-efficacy; financial management behavior